Cardiac surgery in Wessex. Issue 6362 (29th January 1983) - Monro, J L; Ross, J K; Manners, J M; Edwards, J C; Lewis, B; Hyde, I; Ogilvie, B C; Keeton, B R; Conway, N; Johnson, A M
Abstract : The results of 3000 consecutive operations using cardio-pulmonary bypass show that the overall early mortality was 6.1%, dropping from 8.9% in the first 1000 to 4.4% in the third 1000. Operations for valve disease have been the most common, the early mortality for aortic valve replacement being 3.1% and for mitral valve replacement 2.9%. Combined aortic and mitral valve replacement had an early mortality of 4.4%. The number of patients undergoing isolated coronary artery bypass grafting has increased from 59 in the first 1000 to 292 in the third 1000 operations, with an overall early mortality of 1.3%. Six hundred and ninety seven patients underwent surgery for congenital heart disease with an overall early mortality of 10.9% (7.5% in the last 2000 cases). The patients have been followed up from one to 8.5 years. A high proportion have returned to work and enjoy a normal life. At the time of review, 87% of the 3000 patients were alive. Long waiting times for outpatient and inpatient care indicate underprovision of facilities relative to regional demand.